Differential acclimation kinetics of the two forms of type IV chromatic acclimaters occurring in marine Synechococcus cyanobacteria - Dufour, Louison; Garczarek, Laurence; Gouriou, Bastian; Clairet, Julia; Ratin, Morgane; Partensky, Frédéric (Frontiers in Microbiology, 2024)
Synechococcus, the second most abundant marine phytoplanktonic organism, displays the widest variety of pigment content of all marine oxyphototrophs, explaining its ability to colonize all spectral niches occurring in the upper lit layer of oceans. Seven Synechococcus pigment types (PTs) have been described so far based on the phycobiliprotein composition and chromophorylation of their light-harvesting complexes, called phycobilisomes. The most elaborate and abundant PT (3d) in the open ocean consists of cells capable of Type IV chromatic acclimation (CA4), i.e. to reversibly modify the ratio of the blue light-absorbing phycourobilin (PUB) to the green light-absorbing phycoerythrobilin (PEB) in phycobilisome rods to match the ambient light color. Two genetically distinct types of chromatic acclimaters, so-called PTs 3dA and 3dB, occur at similar global abundance in the Ocean, but the precise physiological differences between these two types and the reasons for their complementary niche partitioning in the field remain obscure. Here, photoacclimation experiments in different mixes of blue and green light of representatives of these two PTs demonstrated that they differ by the ratio of blue-to-green light required to trigger the CA4 process. Furthermore, shift experiments between 100% blue and 100% green light, and vice-versa, revealed significant discrepancies between the acclimation pace of the two types of chromatic acclimaters. This study provides novel insights into the finely tuned adaptation mechanisms used by Synechococcus cells to colonize the whole underwater light field.